2021
DOI: 10.11606/s1518-8787.2021055003221
|View full text |Cite
|
Sign up to set email alerts
|

Evolução do consumo de alimentos fora do domicílio no Brasil de 2008–2009 a 2017–2018

Abstract: OBJETIVO Descrever a evolução do consumo de alimentos fora do domicílio no Brasil no período 2008–2018. MÉTODOS Foram usados dados dos Inquéritos Nacionais de Alimentação (INA) de 2008–2009 e 2017–2018, realizados com 34.003 e 46.164 indivíduos, respectivamente, para estimar a frequência de consumo de alimentos fora de casa e a contribuição desse consumo para alimentos específicos. O consumo de alimentos foi investigado por meio de registros alimentares no INA 2008–2009 e de recordatórios 24 horas em 2017–2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
5
1
3
Order By: Relevance
“…The role of Internet use in high-income farm households in improving dietary structure is significantly greater than that in low-income farm households. Equally, in low-income farm households, dietary diversity and dietary rationality are lower than in high-income farm households, similar to the conclusions of Natalia et al ( 93 ).…”
Section: Discussionsupporting
confidence: 85%
“…The role of Internet use in high-income farm households in improving dietary structure is significantly greater than that in low-income farm households. Equally, in low-income farm households, dietary diversity and dietary rationality are lower than in high-income farm households, similar to the conclusions of Natalia et al ( 93 ).…”
Section: Discussionsupporting
confidence: 85%
“…Unlike this study, Bezerra et al. (2021) evaluated the place of consumption considering only the first day of food record or recall in both Brazilian NDS . The authors found a reduction in away‐from‐home eating between the surveys and pointed out that sandwiches, pizza and fried and baked snacks were the food items that fell the most.…”
Section: Discussionmentioning
confidence: 99%
“…Food consumption away from home has been associated with higher energy and fat intake than eating at home (Lachat et al, 2012); moreover, Landais et al (2023) showed that away-from-home food consumption is associated with unfavourable effects on diet quality, nutritional status and health. Unlike this study, Bezerra et al (2021) evaluated the place of consumption considering only the first day of food record or recall in both Brazilian NDS. The authors found a reduction in away-fromhome eating between the surveys and pointed out that sandwiches, pizza and fried and baked snacks were the food items that fell the most.…”
Section: Discussionmentioning
confidence: 99%
“…Although we observed a significant reduction in the purchase of these foods compared to pre-pandemic times, over 60% of participants continued buying them during the pandemic. In Brazil, people most commonly consume fried and baked snacks, pizzas, sweets and sandwiches outside the home, with alcoholic beverages and soft drinks as the most popular drinks (Bezerra et al , 2021). Our findings align with these results, as we found these foods and drinks to be the most frequently purchased both before and during the pandemic.…”
Section: Discussionmentioning
confidence: 99%